"Immuno‐flowFISH" for the Assessment of Cytogenetic Abnormalities in Chronic Lymphocytic Leukemia. Issue 5 (24th April 2019) - Hui, Henry Y.L.; Clarke, Kathryn M.; Fuller, Kathryn A.; Stanley, Jason; Chuah, Hun H.; Ng, Teng Fong; Cheah, Chan; McQuillan, Andrew; Erber, Wendy N.
Abstract: Imaging flow cytometry is emerging as a diagnostic tool for the assessment of leukemia. It has the functionality of standard flow cytometry and generates high‐resolution digital images of each cell with quantifiable numerical data. We demonstrate the use of an automated high‐throughput method for performing fluorescence in situ hybridization (FISH) on immunophenotyped whole cells in suspension and analyzed by imaging flow cytometry, a technique called "Immuno‐flowFISH". The aim of this study was to demonstrate the application of immuno‐flowFISH for the detection of chromosomal abnormalities in CLL, specifically trisomy 12 and del(17p). Mononuclear cells were isolated and immunophenotyped with fluorescently conjugated CD3, CD5, and CD19 monoclonal antibodies. Following fixation, cells were permeabilized, dsDNA denatured and hybridized with chromosome 12 or 17 enumeration (CEP 12 and CEP17) and 17p12 locus‐specific FISH probes. Cells were analyzed on the Amnis ImageStream®X Mark II to assess the number and percent FISH‐positive CLL cells and the ratio of FISH spot counts for CD5/CD19‐positive CLL cells to CD3/CD5‐positive T cells (FISH "mean spot ratio"). Deletion of 17p was detected in about 8% of cases to date, with del(17p) ranged from 3.5–22.8% and the FISH "mean spot ratio" 0.86–0.96. Immuno‐flowFISH also detected a minimal residual disease case with +12 with a limit of detection of 0.13% and a rare case that presented with atypical phenotype and cytogenetics. Immuno‐flowFISH could detect del(17p) in phenotypically identified CD5/CD19‐positive B‐cells. The 100‐fold increase in analyzed cells, as well as the addition of cell phenotype increased the sensitivity and specificity over current clinical FISH testing. Furthermore, immuno‐flowFISH analysis demonstrated specific utility in unique clinical scenarios such as residual disease and atypical biology cases which may be of significant benefit with regards to prognostication and MRD analysis. The method will assist in therapeutic decision making and disease monitoring for many hematological malignancies. © 2019 International Society for Advancement of Cytometry Abstract :